Antioxidant Activity Test (DPPH) and Cytotoxicity of Jengkol Peel Ethanol Extract (Pithecellobium jiringa) on Shrimp Larvae (Artemia salina Leach) - Wibowo, Glen Arya; Afriani, Tika; Rahmi, Azimatur (Biology, Medicine, & Natural Product Chemistry, 2023)
This study aims to determine the antioxidant and cytotoxic activity of the ethanol extract of jengkol peel (Pithecellobium jiringa). Jengkol peel ethanol extract (Pithecellobium jiringa) was obtained by maceration using 70% ethanol as a solvent. In the phytochemical screening test it was found that chemical compounds contained in jengkol peel (Pithecellobium jiringa) including alkaloids, flavonoids, and saponins. The antioxidant activity of the ethanol extract was tested using the 35 ppm DPPH method. The test results on the ethanol extract showed moderate antioxidant activity with an IC50 value of 209.45 Âµg/mL. The cytotoxic activity of the ethanol extract was tested by the BSLT method using shrimp larvae (Artemia salina L.). The results showed that the ethanol extract of jengkol peel (Pithecellobium jiringa) has cytotoxic activity with LC50 value minimum of 17.875 mg/L and LC50 a maximum of 360.714 mg/L with an average of 180.136 mg/L.